Simple modules for groups with abelian Sylow 2-subgroups are algebraic - Craven, D (Elsevier, 2009)
An algebraic module is a KG-module that satisfies a polynomial with integer coefficients, with addition and multiplication given by direct sum and tensor product. In this article we prove that if G is a group with abelian Sylow 2-subgroups and K is a field of characteristic 2, then every simple KG-module is algebraic.